STUDY OF DOSAGE ADJUSTMENT OF ORAL ANTIDIABETIC DRUG IN TYPE II DIABETES MELLITUS PATIENTS WITH DISORDERS KIDNEY FUNCTION AT DR. SOEKARDJO TASIKMALAYA HOSPITAL - Risa Susanti; Doni Anshar Nuari; Sitti Fatimah P.H.; Astrid Fauziyah (Fakultas MIPA Universitas Garut, 2023)
Diabetic nephropathy is one of the complications in DM that can end up becoming DM kidney failure. Nephropathy complications, if not handled properly, will lead to terminal chronic kidney disease. One of the factors that trigger complications of diabetic nephropathy in DM patients is the long-term use of oral anti-diabetic drugs. Therefore, proper dosage adjustment of these antidiabetic drugs, which are excreted through the kidneys, is required. The purpose of this study was to determine whether the dose received by type II DM patients with impaired renal function in the hospital was appropriate or not. This research will be carried out quantitatively and retrospectively by collecting patient medical record data at the hospital, and then the data obtained will be analyzed descriptively by calculating the creatinine clearance using the Cockcroft & Gault formula and comparing it with the literature dose based on the value of creatinine clearance. The sampling technique used was purposive sampling using the inclusion and exclusion criteria determined by the researcher. The inclusion criteria are data on type II diabetes mellitus patients with impaired kidney function at dr. Soekardjo Tasikmalaya Hospital in October–December 2020 who were treated with oral anti-diabetic drugs. The exclusion criteria were type II DM patients with impaired renal function who were treated with insulin, type I DM patients, and type II DM patients with impaired renal function who were treated with oral antidiabetic with incomplete laboratory data. Based on research that has been conducted on 35 samples, as many as 25 people, or 71.43 percent of patients, received therapeutic doses that were not in accordance with their kidney conditions. Meanwhile, 10 people, or 28,57% of patients, received a therapeutic dose according to their kidney condition.